Physical Condition of Pekalongan City Athletes - Jamaludin Yusuf; Setya Rahayu; Oktia Woro Kasmini Handayani; Taufiq Hidayah (International Conference on Science, Education, and Technology, 2023)
The physical condition of an athlete refers to the physical abilities and general health of an athlete in the context of a particular sport or physical activity. An athlete's physical condition is influenced by various factors, including regular and measurable physical exercise, a balanced diet, adequate rest, as well as genetic and environmental factors. Several physical aspect conditions that can affect athlete performance include muscle strength, endurance, speed, and flexibility. All of these aspects must be improved in a balanced way so that an athlete can perform optimally. The physical condition of athletes in Pekalongan City was studied. The population of this study was 49 athletes, and data was obtained through tests and measurements of endurance, speed, flexibility, and arm muscle strength. The average results of the tests showed endurance test was 32.03 in the less category, the speed test was 5.44 in the less category, the flexibility test was 18.45 in the sufficient category, and the arm muscle strength test was 32.31 in. in less categories. In conclusion, the physical condition of Pekalongan city athletes is in the less category.